1994
DOI: 10.1016/0014-5793(94)00872-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two cDNAs encoding for compartment specific isoforms of O‐acetylserine (thiol) lyase from Arabidopsis thaliana

Abstract: cDNAs encoding for two isoforms of O-acetylserine (thiol) lyase (OAS-TL), which catalyzes the synthesis of cysteine, have been isolated from Arabidopsis thaliana. Secondary structure together with expression patterns derived during photomorphogenesis indicate cellular localizations in the cytosol and plastids, thus allowing a direct comparison of compartment-specific forms within one species. The cytosolic OAS-TL complemented an E. coli auxotrophic mutant lacking cysteine synthesis. Both isoforms are represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…We found only slight differences (1.2-to 1.5-fold) in the mRNA level of CysA and CysB in sulfate-starved cells during the starvation periods of 0 to 24 h compared with cells grown in the normal Murashige-Skoog medium. Hell et al (1994) have demonstrated a 1.5-to 2.0-fold up-regulation of these two Cys isoforms in sulfate-starved Arabidopsis seedlings. However, it is questionable that Cys genes respond directly to the exogenous sulfate supply, reflecting the demands of Cys production for protein synthesis in these subcellular compartments to maintain cell activities.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found only slight differences (1.2-to 1.5-fold) in the mRNA level of CysA and CysB in sulfate-starved cells during the starvation periods of 0 to 24 h compared with cells grown in the normal Murashige-Skoog medium. Hell et al (1994) have demonstrated a 1.5-to 2.0-fold up-regulation of these two Cys isoforms in sulfate-starved Arabidopsis seedlings. However, it is questionable that Cys genes respond directly to the exogenous sulfate supply, reflecting the demands of Cys production for protein synthesis in these subcellular compartments to maintain cell activities.…”
Section: Discussionmentioning
confidence: 86%
“…To obtain a comprehensive explanation for the different functional roles of CS isoforms, molecular biologic studies have been initiated. Recently, cDNA clones for the nuclear encoded cytoplasmic, chloroplastic/ plastidic, and putative mitochondrial isoforms have been isolated from various plant species (Romer et al, 1992;Saito et al, 1992Saito et al, , 1993Saito et al, , 1994Hell et al, 1993Hell et al, , 1994Rolland et al, 1993;Youssefian et al, 1993;Noji et al, 1994). We have designated the three genes encoding CS isoforms in spinach as CysA (cytoplasmic) (Saito et al, 1992), CysB (chloroplastic/plastidic) (Saito et al, 1993), and CysC (putative mitochondrial) .…”
Section: -290 -2905mentioning
confidence: 99%
“…The same was true for the oastlAB mutant. The abundance of the five OAS-TL proteins that bound to SAT correlated well with the relative amounts of mRNAs in leaves and roots at this developmental stage in the literature (Hell et al, 1994;Hesse et al, 1999;Hatzfeld et al, 2000;Yamaguchi et al, 2000) and in a public microarray database (Zimmermann et al, 2004).…”
Section: Abundance Of Individual Isoforms and Posttranslational Modifmentioning
confidence: 79%
“…In Arabidopsis thaliana, SAT and OAS-TL proteins are encoded by small gene families and distributed between cytoplasm, mitochondria, and plastids (Hell et al, 1994;Bogdanova et al, 1995;reviewed in Hell et al, 2002;Kawashima et al, 2005). According to the Genevestigator database (Zimmermann et al, 2004), the most strongly transcribed genes, out of nine OASTL-like genes, are OASTLA1 (At4g14880), OASTLB (At2g43750), OASTLC (At3g59760), and CYSC1 (At3g61440).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of OASS in transgenic plants improves heavy metal tolerance (8), increases cysteine biosynthesis in response to sulfur stress (9), and provides protection against oxidative stress (10,11). In Arabidopsis, three tissue-specific OASS isoforms catalyze the formation of cysteine from sulfide and O-acetylserine (12)(13)(14)(15). Likewise, Spinacia oleracea (spinach) expresses a similar set of isoforms (16 -18).…”
mentioning
confidence: 99%